2006
DOI: 10.4028/www.scientific.net/msf.503-504.51
|View full text |Cite
|
Sign up to set email alerts
|

On the Microstructure of HPT Processed Cu under Variation of Deformation Parameters

Abstract: The evolution of strength characteristics and the microstructure of copper subjected to high pressure torsion (HPT) are studied under variation of strain and hydrostatic pressure. Measurements of Multiple X-ray Bragg Profile Analysis (MXPA) yield microstructural parameters like dislocation density and arrangement, as well as crystallite (domain) size and distribution, and long-range internal stresses. TEM investigations are carried out to analyse the structural elements and to compare them with the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Obviously, the same parallelity of strain dependences of T max and external stress was found, as demonstrated by Figure 8 for a pressure of 4 GPa (similar correlations have also been found for 2 and 8 GPa). Even more direct evidence for the strain-dependent change of longrange internal stresses comes from previous X-ray profile analyses, which are shown in Figure 9: [29] The higher is the shear strain accumulated, the higher is the level of internal stresses in parallel to that of the external ones. From a critical shear strain reached, the microstructure starts to recover after HPT.…”
Section: Strain Dependence Of Q Due To Assistance Of Long-range Intermentioning
confidence: 97%
“…Obviously, the same parallelity of strain dependences of T max and external stress was found, as demonstrated by Figure 8 for a pressure of 4 GPa (similar correlations have also been found for 2 and 8 GPa). Even more direct evidence for the strain-dependent change of longrange internal stresses comes from previous X-ray profile analyses, which are shown in Figure 9: [29] The higher is the shear strain accumulated, the higher is the level of internal stresses in parallel to that of the external ones. From a critical shear strain reached, the microstructure starts to recover after HPT.…”
Section: Strain Dependence Of Q Due To Assistance Of Long-range Intermentioning
confidence: 97%
“…It was found that the dislocation density increases with increasing numbers of ECAP passes and saturates after 4-8 passes for both pure fcc metals and solid solutions [45,[65][66][67][68][69][70][71]. As an example, the dislocation density versus the imposed strain for an Al-3% Mg specimen is plotted in Fig.…”
Section: Evolution Of Microstructure During Ecapmentioning
confidence: 99%
“…The size and size-distribution of crystallites, grains, or subgrains, and the dislocation structure were studied intensively in different metals and alloys, e.g. Al [69], Al-alloys [69][70][71], Cu [72][73][74][75][76][77][78], or Ni [79][80][81], processed by SPD procedures at room temperature, e.g. by equal channel angular pressing (ECAP) or high pressure torsion (HPT).…”
Section: 5mentioning
confidence: 99%